Tindak Pidana Kekerasan Dalam Proses Belajar Mengajar Ditinjau Dari Perspektif Hukum Pidana Dan Undang-Undang Nomor 14 Tahun 2005 Tentang Guru Dan Dosen - Aan Hardiansyah; Akhmad Khisni (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
ABSTRACT This research entitled Criminal Violence in Teaching and Learning Process Viewed From Criminal Law Perspective Law Number 14 Year 2005 About Teachers and Lecturers. The purpose of this study: 1) To know and analyze the criminal acts in teaching and learning process in the perspective of criminal law and Law no. Law No. 14 Year 2005 on Teachers and Lecturers. 2) To know and analyze the weaknesses of criminal acts in teaching and learning process in the perspective of criminal law and Law no. Law No. 14 Year 2005 on Teachers and Lecturers. 3) To find out the solution of criminal acts in teaching and learning process in the perspective of criminal law and Law no. Law No. 14 Year 2005 on Teachers and Lecturers.Result of the research: 1) Provision of physical sanctions by teachers to learners in the perspective of criminal law is not a criminal offense and can not be accounted for criminal, as such a physical sanction is a means to improve education and discipline of learners. 2) In today's era of many complaints of teacher violence against students, teachers who provide physical sanctions to students in school is not a criminal offense and can not be held criminally liable as a physical sanction just as a means to educate and discipline students and physical sanctions given in the corridor and fairness limits. 3) The solution of crime in teaching and learning process is: a. Apply nonviolent education. b. Encourage or develop humanization of education. c. The punishment provided correlates with the child's actions. d. Equip teachers with knowledge insights. e. Counseling. f. Immediately provide help to anyone experiencing acts of violence.Keywords : Crime, Violence, Teacher And LecturerABSTRAK Penelitian ini berjudul Tindak Pidana Kekerasan Dalam Proses Belajar Mengajar Ditinjau Dari Perspektif Hukum Pidana Undang-Undang Nomor 14 Tahun 2005 Tentang Guru Dan Dosen. Tujuan Penelitian ini : 1) Untuk mengetahui dan menganalisis tindak pidana dalam proses belajar mengajar dalam perspektif hukum pidana dan Undang-Undang No. 14 Tahun 2005 tentang Guru dan Dosen. 2) Untuk mengetahui dan menganalisis kelemahan-kelemahan tindak pidana dalam proses belajar mengajar dalam perspektif hukum pidana dan Undang-Undang No. 14 Tahun 2005 tentang Guru dan Dosen. 3) Untuk mengetahui solusi tindak pidana dalam proses belajar mengajar dalam perspektif hukum pidana dan Undang-Undang No. 14 Tahun 2005 tentang Guru dan Dosen.Hasil Penelitian : 1) Pemberian sanksi fisik oleh guru kepada peserta didik dalam prespektif hukum pidana bukan merupakan tindak pidana dan tidak dapat dipertanggungjawabkan pidana, semampang sanksi fisik tersebut merupakan sarana untuk meningkatkan edukasi dan kedisiplinan peserta didik. 2) Pada era sekarang ini banyak aduan kekerasan guru terhadap peserta didik, guru yang memberikan sanksi fisik kepada peserta didik di sekolah bukan merupakan tindak pidana dan tidak dapat dimintai pertanggungjawaban pidana semampang sanksi fisik tersebut hanya sebagai sarana untuk mendidik dan mendisiplinkan peserta didik serta sanksi fisik yang diberikan dalam koridor dan batas kewajaran. 3) Solusi tindak pidana dalam proses belajar mengajar adalah : a. Menerapkan pendidikan tanpa kekerasan. b. Mendorong atau mengembangkan humanisasi pendidikan. c. Hukuman yang diberikan berkorelasi dengan tindakan anak. d. Membekali guru dengan wawasan pengetahuan. e. Konseling. f. Segera memberikan pertolongan bagi siapapun yang mengalami tindakan kekerasan.Kata Kunci : Tindak Pidana, Kekerasan, Guru Dan Dosen